Effectiveness of Some Plant Materials against Jute Yellow Mite on Corchorus Olitorius (Journal of Environmental Science and Natural Resources, 2021)
An experiment was conducted to evaluate the effectiveness of plant materials against yellow mite (Polyphagotarsonemus latus) on jute (Corchorus olitorius) cv. 0–9897 in both greenhouse and field condition at BJRI during the period from March to October 2016. In greenhouse premises, the highest mortality (69.39, 67.77, 63.86, 62.43 and 61.47%) was recorded in extract of neem seed kernel @ 1:20, mehogony seed, pithraj seed, turmeric powder and green neem leaf, respectively. In field condition, the highest reduction (70.20%) of infestation over control, lowest nodes plant–1 (52.50), tallest plant (3.10 m) and highest yield increased (38.60%) over control were observed in neem seed kernel extract @ 1:20. In conclusion, neem seed kernel extract, mahogany seed extracts, pithraj seed extract, green neem leaf extract and turmeric powder extract @ 1:20 can be safely used by the farmers as components of IPM program of Jute.Environ. Sci. & Natural Resources, 12(1&2): 165-170, 2019